Computation of ion exchange buried microring resonator waveguide for THz communication applications - Amiri, Iraj Sadegh; Alizadeh, Farideh; Ariannejad, Mohammad Mahdi; Amini, Rahmat; Yupapin, Preecha Promphan (Elsevier, 2018)
The ion exchange creates the optical buried waveguides, whereas it is the method that the glass doping occurs with the condition of existence of the mobile metal ions. The most common ion used is silver (Ag+) due to its broad variation in the refractive index. The proposed application presented in this work is to use the microring resonator (MRR) system based on the buried waveguides simulated by the ion exchange method. The passive MRRs are realized as the multi-wavelength transceiver, applicable in optical technologies such as the optical sensing, Terahertz (THz) communication and optical switching. The cross-sectional view of the simulated buried optical waveguide for the Ag+ concentrations of 0.8 mol/m3 is presented. The fundamental mode propagation is simulated using the time-domain traveling wave method, where the simulation of the optical power flow density and the electric field distributions of the buried waveguides were performed. The two coupled MRRs are used to generate tunable dual-wavelength with spacing in the range of Terahertz (THz). As results, the dual wavelengths in the range between 0.25 and 0.96 THz were generated at the throughput and drop port of the MRRs system.